Characteristics of the CE 1226 Medieval tephra layer from the Reykjanes volcanic system - Agnes Ösp Magnúsdóttir 1985- (2015)
Diskur (Appendix) fylgir prentaða eintakinu sem er varðveitt í Landsbókasafni Íslands - Háskólabókasafni The Medieval tephra layer was formed in an eruption within the Reykjanes volcanic system in the year 1226 CE. It is the largest tephra layer formed in the system and on the Reykjanes peninsula since the settlement of Iceland. The layer has been studied using grain size analysis, particle shape analysis, SEM studies and volume estimates using three different models of tephra layer volumes. Grain size distributions measurements were made for twelve ash samples at various distances from the volcanic source. The grains were analyzed down to 1 µm. Some of the samples were collected from a part of the ash layer but most of them were bulk samples. SEM analysis of representative grains in the phi 3-4 range showed them to have typical characteristics of particles formed in phreatomagmatic eruptions. The amount of fine material preserved in the soil from this phreatomagmatic eruption was small, suggesting that a part of the fine material has been removed by the combined effect of wind and water erosion. Various aspects of the tephra were examined in order to determine whether systematic changes occur with growing distance from source. The total grain size distribution was found using the Voronio method, applied to a series of bulk samples. The median grain size for this tephra layer was found to be 2.4 phi or 189 µm. Shape analysis of the tephra layer was performed by using a particle shape analyzer. Two types of triangular plots were made using different parameters; some of the plots show a slight difference in particle shape between three selected sample places at various distances from the source. Statistical analysis shows that a significant but small changes occur with distance from source in almost all parameters used in the triangular plots. Volume calculations were made using three different methods: The power law, exponential thinning and the Weibull method. The results show that the values obtained for the ...